Generation of a human induced pluripotent stem cell line (UQi001-A-1) edited with the CRISPR-Cas9 system to carry the heterozygous TARDBP c.1144G > A (p.A382T) missense mutation - Timothy J. Tracey; Leanne Jiang; Melinder K. Gill; Samara N. Ranie; Dmitry A. Ovchinnikov; Ernst J. Wolvetang; Shyuan T. Ngo (Stem Cell Research, 2023)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease in which the TDP-43 protein is believed to play a central role in disease pathophysiology. Using the CRISPR-Cas9 system, we introduced the heterozygous c.1144G > A (p.A382T) missense mutation in exon 6 of the TARDBP gene into an iPSC line derived from a healthy individual. These edited iPSCs displayed normal cellular morphology, expressed major pluripotency markers, were capable of tri-lineage differentiation, and possessed a normal karyotype.